Fatigue crack propagation behaviors in Ti-5Al-3Mo-3V-2Zr-2Cr-1Nb-1Fe alloy with STA and BASCA heat treatments. (October 2021) - Wang, Huan; Zhao, Qinyang; Xin, Shewei; Zhao, Yongqing; Huang, Shixing; Zhou, Wei; Zeng, Weidong
Highlights: The differences of the FCP rates in rapid growth regime between EM and LM are owing to the varied fracture modes. The FCP behaviors in near-threshold and Paris regimes are a result of two contributing factors: interface obstacles and crack front profile. Abstract: Fatigue crack propagation behaviors of a novel high strength Ti-5Al-3Mo-3V-2Zr-2Cr-1Nb-1Fe alloy with equiaxed and lamellar microstructures were systematically investigated. Fatigue crack propagation tests at both increasing and decreasing stress intensity factor range values were carried out with a frequency of 15 HZ and stress radio R of 0.1 by using compact tension samples. The sample with lamellar microstructure displayed the faster fatigue crack propagation rates in near-threshold regime compared to the sample with equiaxed microstructure. The fatigue threshold (ΔKth ) was 2.7 MPa·m 1/2 for lamellar microstructure, and 3.2 MPa·m 1/2 for equiaxed microstructure. The steady state crack growth rate in lamellar microstructure was slightly slower than that in equiaxed microstructure in the Paris regime, while much faster in the rapid growth regime. The interactions between crack path and microstructures as well as the microscopic fracture surface morphology in both microstructures were detected and analyzed by scanning electron microscope (SEM), revealing the different crack propagation behaviors in three regimes. The results showed that the crack propagation behaviors were a result of two contributing factors: interface obstacles and crack front profile. The increased fatigue crack propagation resistance of equiaxed microstructure in near-threshold regime can be attributed to the interface obstacles which dominated over the rougher crack front profile. While the higher fatigue crack growth resistance for lamellar microstructure in Paris regime was attributed to the more positive effect of rougher crack front profile. In the rapid growth regime, the crack in lamellar microstructure was found to be extended along the grain boundary α, which was regarded as a low energy crack path and led to the faster crack propagation rate.